EP855 Metachronous brain metastases in ovarian cancer. (1st November 2019) - Ghidhaoui, A; Staebler, A; Schittenhelm, J; Brucker, S; Bachmann, C
Abstract : Introduction/Background: Brain metastasis (BM) from ovarian cancer is a rare disease leading to limited survival. Aim is to evaluate risk factors and survival for BM from epithelial ovarian cancer (EOC). Methodology: A total of 24 patients diagnosed with metachronous BM after therapy of primary ovarian cancer treated at university Tuebingen from 01/2000 to 3/2019, were retrospectively analyzed. Results: Age at first diagnosis was 56 years (range 42–71 y) in median; 83, 3% had advanced FIGO stages (III/IV); 22 patients had histologic grade 2/3. 46%: node-negative; 46%: node-positive; 8%: Nx. All patients received adjuvant platinum-based chemotherapy ± bevacizumab according to guidelines. At primary surgery, 58.3% achieved complete cytoreduction (R=0 mm), 25.0%: R>0 mm-<1 cm, 4.2%: R≥1 cm, 12.5%: Rx. 12 patients had recurrence of disease. 22 (91, 7%) patients had extracranial disease. At diagnosis of BM all patients received whole-brain radiotherapy; 5 obtained additionally neurosurgical intervention. Most common distant metastatic site was lymph nodes, followed by liver, lung and bone. Overall, interval from first diagnosis to occurrence of BM was 39 months in median (range 10–98 months). Overall survival from first diagnosis of ovarian cancer was 46 months in median (range 13–108 months) and after diagnosis of BM was 10 months (range 1–84 months). After complete cytoreduction interval to BM was 46.9 months (range 11–98) in median, after R>0 mm BM were detected after 30 months in median (range 10–52). In women without extracranial disease, interval from first diagnosis to BM was 31.5 months in median (range 14–49), in women with extracranial disease this timespan was 39, 7 months median (range 10–98). 17 women with extracranial metastases died of disease. Conclusion: Despite presenting a rare manifestation of ovarian cancer, development of BM should be considered in advanced ovarian cancer. Presence of extracranial disease was associated with poor survival in patients with BM and leads to longer interval to occurrence of BM. Disclosure: All authors declare that there is no potential conflict of interest.